2015
DOI: 10.1007/s00586-015-4038-3
|View full text |Cite
|
Sign up to set email alerts
|

Complex cervical spondylotic myelopathy: a report of two cases and literature review

Abstract: Posterior surgical approach as C1-7 laminectomy with fixations or occipital-cervical fusions may obtain better reconstructions of the cervical spine and good neurological recovery for the patients with complex CSM we present. However, the incidence and ethnic predisposition for the patients with complex CSM are still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In general, the posterior approach is used to treat degeneration of multisegmental cervical vertebrae ( 17 ), as the anterior approach is technically challenging and may cause spinal cord damage. In the event of segmental instability, posterior lateral mass or pedicle screw fixation may be used ( 21 , 22 ). Although studies have reported patients who have clinically good outcomes with anterior segmental decompression with preservation of a portion of the posterior vertebral wall ( 23 , 24 ), the MRI and clinical observation of patients undergoing the posterior approach suggest that the spinal cord is also completely decompressed under the anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the posterior approach is used to treat degeneration of multisegmental cervical vertebrae ( 17 ), as the anterior approach is technically challenging and may cause spinal cord damage. In the event of segmental instability, posterior lateral mass or pedicle screw fixation may be used ( 21 , 22 ). Although studies have reported patients who have clinically good outcomes with anterior segmental decompression with preservation of a portion of the posterior vertebral wall ( 23 , 24 ), the MRI and clinical observation of patients undergoing the posterior approach suggest that the spinal cord is also completely decompressed under the anterior approach.…”
Section: Discussionmentioning
confidence: 99%